Dampak Penggunaan Disfemisme Para Gamers Pada Media Sosial Youtube - ., Rina; Tanduk, Rita; Gasong, Dina (Jurnal Pendidikan, Sains Dan Teknologi, 2024)
The aim of this research is to explain the form and meaning of dysphemism expressions in content created by gamers on YouTube social media channels and to explain the impact of the use of dysphemism on the implications of character education. The type of research used is a qualitative descriptive method. Data collection procedures were carried out using tapping, note-taking and documentation techniques. The data analysis method used in this research uses descriptive analysis techniques with the triangulation method. The research results found in this study concluded that the use of dysphemism by game content creators on their YouTube channels contained five types of dysphemism expressions including; (a) the use of taboo terms, such as words that cannot be said, taboos, or prohibitions; (b) obscene cursing and swearing; (c) comparison of humans with animals; (d) nicknames or greetings related to human physical characteristics; and (e) terms of ridicule and disrespect towards someone. Meanwhile, the impact of dysphemism on character education in this research is in the form of; (1) Violation of religious values; (2) violation of the value of love of peace; (3) violation of the value of responsibility.